Upconversion/Downshifting Multimode Luminescence of Lanthanide‐doped Nanocrystals for Multidimensional Information Encoding Security. Issue 17 (12th July 2022) - Song, Yapai; Sun, Renrui; Sun, Guotao; Xie, Yao; Sun, Lining
Abstract: Information encoding security has always been a research hotspot in the optical field. Although many studies focused on luminescent materials and techniques for information security, the optical information encoding is limited by low information capacity and security. Herein, we present new core‐shell‐shell (CSS) lanthanide‐doped nanocrystals which display multi‐stimuli‐responsive and multimode emission. In the designed CSS nanostructure, the Stokes and anti‐Stokes processes can be both achieved in the same nanocrystals under the excitation of 1532, 980, and 254 nm via self‐excited Er 3+ and Ce 3+ ‐sensitized mechanisms. Subsequently, a group of unique multimode emission CSS nanocrystals were designed as optical modules and successfully utilized in multidimensional information encoding, which demonstrates high‐level information encoding capability and security. This work brings a powerful idea for information encoding security designs based on multimode luminesce materials. Abstract : Stokes and anti‐Stokes processes can be both achieved in designed core‐shell‐shell (CSS) lanthanide‐doped nanocrystals which display multi‐stimuli‐responsive and multimode emission. Subsequently, a group of unique multimode emission CSS nanocrystals were designed as optical modules and successfully utilized in multidimensional information encoding.